Analysis of The Implementation of Organic Waste Management Policy - Zaini, Zaman; Sukmawati, Sonia; Tuswoyo, Tuswoyo; Junaidi, Ahmad (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2023)
The background of this research isthephenomenonoftheuniquemanagementoforganicwaste. The activityiscarriedby